Technology of Increasing the Service Period of Liquidation Furnaces Based Liquid Shibba - Bekchanova Valida; Turakhodjaev Nodir; Chorshanbiyeva Lobar; Gulyamov Saidsulton; Urinboyev Umidjon, Eshimov Doston (Genius Journals, 2023)
This research analyze the effect of slag and metal composition in electric arc furnace, and the factory data is statistically evaluated according to the degree of corrosion of refractory lining. The degree of corrosion of the lining in an electric arc furnace under the influence of special slag (basic CaO, MgO, FeO, Al2O3, SiO2) and metal components (C, Mn) were analyzed at the factory. In these factories, together with the corrosion data, the values of the slag composition were represented by a diagram in relation to the oxidation potential between basic, acidic and oxides
Keywords: steel; wear; resistance; refractory lining